Methionine Cycle Rewiring by Targeting miR-873-5p Modulates Ammonia Metabolism to Protect the Liver from Acetaminophen - Rodríguez-Agudo, Rubén; Goikoetxea-Usandizaga, Naroa; Serrano-Maciá, Marina; Fernández-Tussy, Pablo; Fernández-Ramos, David; Lachiondo-Ortega, Sofía; González-Recio, Irene; Gil-Pitarch, Clàudia; Mercado-Gómez, María; Bizkarguenaga, Maider; Lopitz-Otsoa, Fernando; Petrov, Petar; et al. (IOAP-MPDI, 2022)
Drug-induced liver injury (DILI) development is commonly associated with acetaminophen (APAP) overdose, where glutathione scavenging leads to mitochondrial dysfunction and hepatocyte death. DILI is a severe disorder without effective late-stage treatment, since N-acetyl cysteine must be administered 8 h after overdose to be efficient. Ammonia homeostasis is altered during liver diseases and, during DILI, it is accompanied by decreased glycine N-methyltransferase (GNMT) expression and S-adenosylmethionine (AdoMet) levels that suggest a reduced methionine cycle. Anti-miR-873-5p treatment prevents cell death in primary hepatocytes and the appearance of necrotic areas in liver from APAP-administered mice. In our study, we demonstrate a GNMT and methionine cycle activity restoration by the anti-miR-873-5p that reduces mitochondrial dysfunction and oxidative stress. The lack of hyperammoniemia caused by the therapy results in a decreased urea cycle, enhancing the synthesis of polyamines from ornithine and AdoMet and thus impacting the observed recovery of mitochondria and hepatocyte proliferation for regeneration. In summary, anti-miR-873-5p appears to be an effective therapy against APAP-induced liver injury, where the restoration of GNMT and the methionine cycle may prevent mitochondrial dysfunction while activating hepatocyte proliferative response.
Keywords: Paracetamol; Drug-induced liver injury (DILI); Acetaminophen (APAP); Ammonia; Methionine cycle; MiR-873-5p; Therapy; Polyamines